Does Vacuum-assisted Closure Reduce the Risk of Wound Complications in Patients With Lower Extremity Sarcomas Treated With Preoperative Radiation?. Issue 4 (April 2019) - Bedi, Meena; King, David M.; DeVries, John; Hackbarth, Donald A.; Neilson, John C.
Abstract: Background: Although preoperative radiation followed by wide local excision yields excellent local control in soft tissue sarcomas, the risk of wound complications is reported to be higher compared with the incidence in patients who were administered postoperative radiation therapy. Vacuum (vac)-assisted closure may improve wound healing, but it is unknown whether vac-assisted closure during soft tissue sarcoma resection may reduce the risk of wound complications or impair local disease control. Questions/purposes: (1) Does the use of a wound vac application at the time of soft tissue sarcoma resection reduce the risk of developing wound complications after lower extremity sarcoma resection? (2) Is vac-assisted closure associated with an increased risk of local relapse? Methods: From 2000 to 2016, 312 patients with stage I to III soft tissue sarcomas were treated. Of these, 123 were treated with preoperative radiation ± chemotherapy followed by limb-sparing resection based on tumor location, size, grade, histology, and patient age. There was a minimum followup of 12 months. Radiation was delivered generally based on tumor size, grade, superficial versus deep nature, and proximity to neurovascular structures. Chemotherapy was administered in patients < 70 years old with high-grade tumors and tumors > 5 cm. Patient, demographic, and treatment variables, including incisional vac application and wound outcomes, were retrospectively evaluated. Incisional vac-assisted closure took place at the time of primary resection in 32% (46 of 123) of patients. Vac-assisted closure was considered when there was a concern for risk of external contamination such as instances in which fixation of adhesives would be difficult or regions where there was a high risk of contamination. Vac-assisted closure may have also been used in instances with increased wound tension at closure or with heightened concern for shearing on the wound such as buttock wounds. Ten patients were lost to followup, two in the vac group and eight in the non-vac group. Potential factors associated with wound complications were evaluated using Fisher's exact test for univariate analysis and logistic regression for multivariate analysis. Local recurrence-free survival was evaluated using the Kaplan-Meier estimate. Results: After taking into consideration factors such as tumor size, location, age, and patient comorbidities, it was shown that patients who underwent vac-assisted closure were less likely to experience wound complications compared with patients who did not undergo vac-assisted closure (odds ratio, 0.129; 95% confidence interval [CI], 0.041-0.398; p = 0.004). The local control incidence in the entire cohort was 98%. With the numbers available, Kaplan-Meier survivorship free from local recurrence did not differ between patients treated with or without the vac (100% [95% CI, 154.09-154.09] versus 96% [95% CI, 152.21-169.16]; p = 0.211), respectively. Conclusions: Vac-assisted closure at the time of resection of proximal lower extremity soft tissue sarcomas is associated with a lower risk of wound complications, and its use apparently did not compromise local control. We show that the use of vac-assisted closure may be worth considering in surgeons' attempts to reduce the risk of wound complications among patients with soft tissue sarcomas of the proximal lower extremities. Level of Evidence: Level III, therapeutic study.